Relevance of host tau in tau seeding and spreading in tauopathies. (27th August 2019) - Ferrer, Isidro; Zelaya, Maria Victoria; Aguiló García, Meritxell; Carmona, Margarita; López‐González, Irene; Andrés‐Benito, Pol; Lidón, Laia; Gavín, Rosalina; Garcia‐Esparcia, Paula; del Rio, José Antonio
Abstract: Human tau seeding and spreading occur following intracerebral inoculation of brain homogenates obtained from tauopathies in transgenic mice expressing natural or mutant tau, and in wild‐type (WT) mice. The present study was geared to learning about the patterns of tau seeding, the cells involved and the characteristics of tau following intracerebral inoculation of homogenates from primary age‐related tauopathy (PART: neuronal 4Rtau and 3Rtau), aging‐related tau astrogliopathy (ARTAG: astrocytic 4Rtau) and globular glial tauopathy (GGT: 4Rtau with neuronal deposits and specific tau inclusions in astrocytes and oligodendrocytes). For this purpose, young and adult WT mice were inoculated unilaterally in the hippocampus or in the lateral corpus callosum with sarkosyl‐insoluble fractions from PART, ARTAG and GGT cases, and were killed at variable periods of three to seven months. Brains were processed for immunohistochemistry in paraffin sections. Tau seeding occurred in the ipsilateral hippocampus and corpus callosum and spread to the septal nuclei, periventricular hypothalamus and contralateral corpus callosum, respectively. Tau deposits were mainly found in neurons, oligodendrocytes and threads; the deposits were diffuse or granular, composed of phosphorylated tau, tau with abnormal conformation and 3Rtau and 4Rtau independently of the type of tauopathy. Truncated tau at the aspartic acid 421 and ubiquitination were absent. Tau deposits had the characteristics of pre‐tangles. A percentage of intracellular tau deposits co‐localized with active (phosphorylated) tau kinases p38 and ERK 1/2. Present study shows that seeding and spreading of human tau into the brain of WT mice involves neurons and glial cells, mainly oligodendrocytes, thereby supporting the idea of a primary role of oligodendrogliopathy, together with neuronopathy, in the progression of tauopathies. In addition, it suggests that human tau inoculation modifies murine tau metabolism with the production and deposition of 3Rtau and 4Rtau, and by activation of specific tau kinases in affected cells.